(untitled) (International scientific-electronic journal “Pioneering studies and theories”, 2025)
Digital banking innovations have soared in the last few years, bringing a wave of transformation to the financial services industry. Customer satisfaction can prove to be a key to long term success. Nonetheless, the established approaches for measuring customer satisfaction are primarily based on traditional service quality concepts and do not appropriately accommodate the specific characteristics associated with digital banking experiences. They allow to existing both customer satisfaction measurement models and the evaluation of innovations. Based on existing theories like SERVQUAL and Technology Acceptance Model (TAM), the proposed framework combines survey-based measures, behavioral data analytics, sentiment analysis, and econometric modeling.